Penerapan Kebijakan Penghapusan Sanksi Administrasi Pajak Kendaraan Bermotor di Kota Jakarta Selatan Tahun 2019 - Bhakti Nur Avianto; Muhammad Hasbi (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The Provincial Government of DKI Jakarta issued Governor Regulation Number 3 of 2018 concerning the elimination of tax administration sanctions (sunset policy) or better known to the public by bleaching. The end of 2019 there were still PKB and BBN arrears, particularly in the South Jakarta City area reaching 15 billion. The results showed the realization of motor vehicle tax revenue of Rp 115,917,771,730, - there was a reduction of Rp 108,247,742,466, - meaning there were still motor vehicle tax arrears of around 7.5 billion. This problem arises because the socialization of bleaching information is still not optimal, the low public interest in the program, and the low tax compliance. This statement emerged from the results of a survey of respondents who stated that the responsive attitude to the sunset policy reached 88.5%, of which 47.9% stated the respondents agreed to the policy of eliminating motor vehicle administration sanctions but they had not used it, in other words, the sunset policy make public interest to obey pay taxes increases. So that the important role of the DKI Jakarta Regional Tax and Retribution Agency (BPRD) will immediately improve tax administration, improve services, systematically and continuously educate taxpayers and ensure law enforcement.